Inflation inequality in Denmark - Andreas Kuchler; Tobias Renkin; Christoffer Jessen Weissert (Danmarks Nationalbank, 2023)
We analyse differences in inflation rates between poor and rich households that arise from heterogeneity in household consumption baskets. Over the 1996 – 2020 period, inflation differences by income are small. From 2020 on, inflation has been about 3pp higher at the bottom of the income distribution than at the top, driven by large price increases in energy and food, which are more important for the consumption baskets of the poor.
Keywords: 330; Inflationsrate; Privater Konsum; Einkommensverteilung; Dänemark